Produção de biocarvão a partir de resíduos de casca de banana e melancia: um estudo sobre carbonização hidrotérmica e pirólise assistida por micro-ondas. - Dinis, Calton João (2025)
Biochar, a carbon-rich material, has gained increasing attention in the fields of agriculture, waste management, and climate change mitigation due to its ability to improve soil quality, store carbon, and reduce greenhouse gas emissions. Faced with challenges posed by the growing global population and the reduction of arable land, biochar stands out as a sustainable solution, applicable as a soil amendment and adsorbent for contaminant removal. This study explores the potential of watermelon and banana peels as lignocellulosic biomasses for thermochemical conversion processes, focusing on the production of biochars through Hydrothermal Carbonization (HTC) and Microwave-Assisted Pyrolysis (MAP). Hydrothermal Carbonization (HTC) emerges as a promising technology for repurposing these residues. Based on moderate temperatures and high pressures, this wet process utilizes water from the biomass, which reaches a subcritical state in the reactor, facilitating the breakdown of cellulose, hemicellulose, and lignin fibers. This method mimics the natural formation of coal and produces hydrochars with specific characteristics. In this study, the hydrochar obtained via HTC demonstrated a solid yield of up to 63.44%, oxygenated functional groups (OFG) content of 5.50 mmol/g, and a BET surface area of 5.16 m²/g, highlighting its applicability as an adsorbent. On the other hand, Microwave-Assisted Pyrolysis (MAP) uses microwave radiation to rapidly heat biomass in an oxygen-free environment, promoting thermal decomposition. This process is characterized by high energy efficiency and precise control over heating parameters, resulting in biochars with a composition enriched in nitrogen (7.93%), phosphorus (0.48%), and potassium (7.62%), with a solid yield of up to 74%, making them ideal for application as biofertilizers. The variables studied included temperature (°C), the ratio between the biomasses (watermelon peel as biomass 1 and banana peel as biomass 2), and time (min). Comparative results show that HTC, due to its high OFG content, is more suitable for adsorbent production, while MAP, with its NPK-rich composition, is recommended for agricultural applications. This study underscores the role of biochar as a sustainable and efficient alternative to mitigate the environmental impacts of inadequate agro-industrial waste management, promoting sustainability in waste management and soil quality improvement.